2014
DOI: 10.1124/mol.113.090951
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effects ofβ1-Adrenergic Receptor Blockers and Polymorphisms on Cardiac Myocyte Ca2+Handling

Abstract: b-Adrenergic receptor blockers (b-blockers) are commonly used to treat heart failure, but the biologic mechanisms governing their efficacy are still poorly understood. The complexity of b-adrenergic signaling coupled with the influence of receptor polymorphisms makes it difficult to intuit the effect of b-blockers on cardiac physiology. While some studies indicate that b-blockers are efficacious by inhibiting b-adrenergic signaling, other studies suggest that they work by maintaining b-adrenergic responsivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…These include more detail on metabolic changes underlying forms of arrhythmia and more detail on the feedbacks by which electrical and ionic changes might be involved longer-term in controlling gene expression (electrotranscription coupling). These alternative mechanisms have been attempted elsewhere, for instance inclusion of binding kinetics [52] , gene expression [109] , safety pharmacology [110] , influence of beta-adrenergic activity [111] and cell signalling 112 , 113 . Because we are already faced with problems of under-determination in the more-complex models, how can these additional demands be compatible with the need for mathematical reduction to simpler models?…”
Section: Discussionmentioning
confidence: 99%
“…These include more detail on metabolic changes underlying forms of arrhythmia and more detail on the feedbacks by which electrical and ionic changes might be involved longer-term in controlling gene expression (electrotranscription coupling). These alternative mechanisms have been attempted elsewhere, for instance inclusion of binding kinetics [52] , gene expression [109] , safety pharmacology [110] , influence of beta-adrenergic activity [111] and cell signalling 112 , 113 . Because we are already faced with problems of under-determination in the more-complex models, how can these additional demands be compatible with the need for mathematical reduction to simpler models?…”
Section: Discussionmentioning
confidence: 99%
“…Metoprolol, one of the most commonly prescribed beta-blockers, exerts its pharmacological effects through the inhibition of adrenergic receptors. 35 Many large-scale clinical trials, including the CIBISII, the MERIT-HF, and the COPERNICUS trial, have demonstrated that the long-term use of a BB in patients with heart failure reduces overall mortality, cardiovascular mortality, and the risk of sudden cardiac death. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies mainly focused on the role of ADRB1 gene in the pathogenesis of disease, and it has been found that ADRB1 polymorphisms are related to various diseases [ 34 39 ]. Researches also found that the rs1801253 polymorphism was related with beta-blocker response [ 40 43 ]. This suggested to us that the rs1801253 has become increasingly important in the reaction to pain, and might be associated with analgesic effect.…”
Section: Discussionmentioning
confidence: 99%